Global Liver Cancer Incidence and Mortality Rates, the Role of Human Development Index - Soheylizad, Mokhtar; Mansori, Kamyar; Ayubi, Erfan; Jenabi, Ensiyeh; Veisani, Yousef; Khosravi Shadmani, Fatemeh; Mansouri Hanis, Shiva; Moradi, Yousef; Khazaei, Salman (Asian Pacific Journal of Cancer Biology, 2016)
Introduction: Liver cancer (LC) is one of the most common malignant tumors worldwide which have been a major public health challenge worldwide. This study aimed to identify the global effect of HDI in the incidence and mortality rates of liver LC. Material and Methods: Data about the incidence and mortality rate of LC for the year 2012 was obtained from the global cancer project for 172 countries. Data about the HDI and other indices were obtained for 169 countries from the United Nations Development Programme database in 2012. Linear regression models were used for assessment of the HDI effect on LC occurrence rates. Inequality in the age-specific incidence and mortality rates (ASR) of LC according to the HDI were assessed by using the concentration index. Results: Linear regression model showed that increasing of HDI had a negative effect on the increase in both incidence (B=-12.2, P=0.03) and mortality (B=-12.7, P=0.015) rates of LC. The mean of life expectancy at birth, mean years of schooling, GNI per capita, percent of urbanization, and age-standardized obesity had also a negative effect on increasing in both incidence and mortality rates. Conclusion: incidence and mortality rate of LC are significantly concentrated in regions with medium and low HDI. The negative relationship between LC incidence and mortality with HDI and its component can be considered as targets for prevention and treatment intervention or tracking geographic disparities.